2020
DOI: 10.1177/1077559520971362
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior Problems Among Sexually Abused Children: Associations With Co-Occurring Symptoms

Abstract: Sexual behavior problems (SBPs) and interpersonal SBPs (ISBPs) among sexually abused children often occur alongside a variety of other clinical difficulties, such as externalizing problems, attentional difficulties, social concerns, and posttraumatic stress symptoms (PTSS). Yet, as few studies have examined these links in a multivariate manner, it is unclear which symptoms are most strongly related to SBPs and ISBPs. Research regarding children’s reports of their difficulties and SBPs and ISBPs is also very li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The present study investigated potential risk factors for children's SBPs that have received less attention, including parenting attitudes and behaviors, family functioning, and help‐seeking. Moreover, although prior research has attempted to identify links between maltreatment types and SBPs, this approach has overlooked the majority of children who have experienced several forms of maltreatment (Allen, 2017; Lussier et al., 2019) while accounting for the importance of children's emotional and behavioral difficulties (Elkovitch et al., 2009; Wamser‐Nanney & Campbell, 2020b). Finally, the current study expands the prior literature by including an examination of ISBPs as a distinct SBP subtype, as suggested in preliminary work (Allen, 2017; Wamser‐Nanney & Campbell, 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study investigated potential risk factors for children's SBPs that have received less attention, including parenting attitudes and behaviors, family functioning, and help‐seeking. Moreover, although prior research has attempted to identify links between maltreatment types and SBPs, this approach has overlooked the majority of children who have experienced several forms of maltreatment (Allen, 2017; Lussier et al., 2019) while accounting for the importance of children's emotional and behavioral difficulties (Elkovitch et al., 2009; Wamser‐Nanney & Campbell, 2020b). Finally, the current study expands the prior literature by including an examination of ISBPs as a distinct SBP subtype, as suggested in preliminary work (Allen, 2017; Wamser‐Nanney & Campbell, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 7%–22% of children in clinical samples (Allen, 2017; Gray et al., 1997) and 10%–47% of sexually abused children and those in the child welfare system (Baker et al., 2008; Wamser‐Nanney & Campbell, 2019, 2020a, 2020b) exhibit sexual behavior problems (SBPs), defined as age‐inappropriate, problematic, or potentially harmful sexual behaviors that may be self‐ or other‐directed and occur in children 12 years of age and younger (Chaffin et al., 2008; Shawler et al., 2018; Smith et al., 2019). Children with SBPs have experienced high rates of maltreatment (i.e., 52%–63%), yet research has focused almost solely on the contribution of individual maltreatment types, overlooking the potential importance of multiple victimization experiences, which often co‐occur (Elkovitch et al., 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SC, including preoccupation with sex or recurrent self-stimulation, can be a consequence of sexual abuse; there is evidence that YSH have many of these residual behavioral and emotional concerns resulting from sexual abuse (Burton et al, 2002; Grabell & Knight, 2009). In fact, researchers have found such trauma-related SC to be particularly salient in associating with sexual behavior problems among children who have been sexually abused (Wamser-Nanney & Campbell, 2020). Although trauma-related SC can co-occur with other trauma symptomatology (e.g., nightmares), researchers have yet to determine their relative effects on executive functioning deficits; trauma-related SC and other trauma symptoms may be discrete but related constructs (Smiljanich & Briere, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Silovsky and Niec (2002) found that, of 13 cases of preschool children displaying PSB and having a CSA history, only two met diagnostic criteria for PTSD. Using continuous measures, Allen (2017) observed only weak evidence linking PTS to the display of PSB among CSA survivors and Wamser-Nanney and Campbell (2022) found that PTS did not explain the connection between CSA and PSB. Data from Simon and Feiring (2008) suggested the opposite effect, that PTS, particularly posttraumatic avoidance of sexual topics, may predict lower rates of PSB among children with CSA histories.…”
mentioning
confidence: 96%